2018
DOI: 10.19102/icrm.2018.090805
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Radiation in the Modern Electrophysiology Laboratory

Abstract: Historically, the electrophysiology laboratory has relied heavily on the use of ionizing radiation in the form of fluoroscopy for a broad range of interventions and diagnostics. As the harmful effects of radiation have become increasingly recognized and procedural technologies have advanced, electrophysiologists have adopted new workflows. The purpose of this article is to review the available literature and experience in minimizing radiation in the modern electrophysiology laboratory. This review first covers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
7
0
4
Order By: Relevance
“…It has been widely shown that obesity has a major impact on radiation exposure of both patients and the operator [22,23]. Reduction of radiation with special protocols and being aware of different radiation exposure in different system angulations is important for every intervention but must especially kept in mind in obese patients [24,25]. In our laboratory we reduce the frame rate per second (fps) to 3 fps whenever possible, collimate the beam, keep the distance of the detector and the patient as low as possible and try to store taken fluoroscopy loops instead of filming again.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely shown that obesity has a major impact on radiation exposure of both patients and the operator [22,23]. Reduction of radiation with special protocols and being aware of different radiation exposure in different system angulations is important for every intervention but must especially kept in mind in obese patients [24,25]. In our laboratory we reduce the frame rate per second (fps) to 3 fps whenever possible, collimate the beam, keep the distance of the detector and the patient as low as possible and try to store taken fluoroscopy loops instead of filming again.…”
Section: Discussionmentioning
confidence: 99%
“…All the procedures were performed in the same electrophysiology laboratory using the Philips Allura Xper FD 10 system (Philips Healthcare, Best, the Netherlands). Electroanatomic mapping was done using the Carto system (Biosense Webster, CA, USA) 2,3 …”
Section: Methodsmentioning
confidence: 99%
“…Electroanatomic mapping was done using the Carto system (Biosense Webster, CA, USA). 2,3 The effective dose (ED, in mSv) was derived from DAP values provided by the X-ray system by multiplying it with a conversion factor. The conversion factors used for adult males and females were 0.2 and 0.28, respectively.…”
Section: Me Thodsmentioning
confidence: 99%
“…It is within this context that Rogers and Brodt 16 provide a well-written and important narrative review that discusses the potential hazards of ionizing radiation exposure, general approaches for decreasing fluoroscopy, and specific task-based alternatives to fluoroscopy. This is a must-read for a cardiologist and especially the proceduralist.…”
Section: "Zero" or "Near-zero" Fluoroscopymentioning
confidence: 99%